Aid allocation decisions of bilateral donors in Ugandan context. Issue 1 (31st December 2022) - Lee, Hyejin
ABSTRACT: Aid allocations choices bilateral donors make can be influenced by the institutional environment of a recipient government and the way this environment is perceived. This study examines bilateral donors' approaches to their aid allocations in Uganda. Uganda provides an interesting case study since the government's control over the aid funds decreased considerably over the past decade-with donors significantly tightening aid fungibility while the total aid funds Uganda received increased compared with the previous decade, 2002–2009. The donors seemed to control aid fungibility through aid modalities, sectors and/or channels; most aid was carried out as projects, in health-related sectors and through non-state actors, leaving small leverage for the Ugandan government over the aid funds. These might be the donors' tactical responses to the cloudy political environment of Uganda by increasing their supervision over the aid funds, instead of cutting them. The largest donor, the United States, mostly shaped the aid portfolio of Uganda showing specific preferences in aid modalities, sectors and channels. Uganda should refine its effort towards an improvement of the national political context. This would increase donors' confidence and willingness to loosen aid fungibility and lead better use of aid resources.